Single-centre experience with anti-tumour necrosis factor treatment in budesonide-refractory microscopic colitis patients. Issue 9 (November 2019) - Daferera, Niki; Hjortswang, Henrik; Ignatova, Simone; Münch, Andreas
Background: Microscopic colitis is an inflammatory bowel disease that causes chronic, watery diarrhoea. Microscopic colitis is usually effectively treated with budesonide, but some patients are refractory. Data on alternative treatments are sparse. Aims: The purpose of this study was to retrospectively evaluate outcome of microscopic colitis patients receiving anti-tumour necrosis factor therapy at our centre. Methods: Treatment results, including side effects, for all microscopic colitis patients receiving anti-tumour necrosis factor therapy were registered at week 12 and at end of follow-up. Clinical remission was defined as a mean of <3 stools and <1 watery stools/day/week and clinical response as a 50% reduction of mean stool frequency/day/week. Induction and maintenance treatment was either adalimumab or infliximab. Results: The study cohort comprised 18 patients; mean age at diagnosis was 47 years (range 19–77). Ten and eight patients, respectively, received adalimumab and infliximab as first-line anti-tumour necrosis factor; seven patients received second-line anti-tumour necrosis factor due to non-response, loss of response or side effects. At week 12, 9/18 patients had achieved remission, 6/18 were responders and 3/18 were non-responders. Of the nine remission patients, 3/18 (16%) had long-lasting clinical remission post-induction therapy alone. Five patients (28%) (one first-line, four second-line anti-tumour necrosis factor) were in remission and one patient (6%) responded to maintenance treatment; follow-up was mean 22 (range 4–60) months. Six patients (33%) had minor, reversible side effects. Conclusions: Over half of budesonide-refractory microscopic colitis patients can achieve clinical remission or response on anti-tumour necrosis factor agents. Prospective studies are mandatory to evaluate the efficacy and safety of anti-tumour necrosis factor treatments in budesonide-refractory microscopic colitis.